Prevalence and Pattern of Mandibular Third Molar Impaction: A Retrospective Radiographic Study - R Nair , Vedha; Anand M , Vijay (Journal of Neonatal Surgery, 2024)
Introduction Mandibular third molars are the most commonly impacted teeth in the oral cavity and are frequently associated with various pathological conditions such as pericoronitis, dental caries, periodontal defects, cyst formation, and root resorption of adjacent teeth. The prevalence and pattern of third molar impaction vary among different populations due to racial, genetic, and environmental influences. Radiographic assessment of impacted mandibular third molars plays a crucial role in diagnosis, treatment planning, and prediction of surgical difficulty. Aim To evaluate the prevalence and pattern of mandibular third molar impaction among the Chennai population and to assess the association between gender and type of impaction using panoramic radiographs. Materials and Methods This retrospective radiographic study included 200 orthopantomograms comprising 100 males and 100 females who reported to Saveetha Dental College and Hospitals. Mandibular third molar impactions were classified according to Winter’s classification as horizontal, mesioangular, vertical, and distoangular impactions. The angulation of impaction was assessed using Quek et al. measurements. Data were analyzed using SPSS version 23.0. Descriptive statistics, Chi-square test, and Odds Ratio analysis were performed to evaluate the association between gender and impaction pattern. A p-value less than 0.05 was considered statistically significant. Results Horizontal impaction was found to be the most prevalent type of mandibular third molar impaction (39.5%), followed closely by mesioangular impaction (37%), vertical impaction (13%), and distoangular impaction (10.5%). Among females, mesioangular impaction was the most common type (44%), whereas horizontal impaction predominated among males (53%). Chi-square analysis demonstrated a statistically significant association between gender and type of impaction (χ² = 16.63, p = 0.001). Odds Ratio analysis revealed that males were approximately 3.4 times more likely to exhibit horizontal impaction compared to females (OR = 3.38). Conclusion Horizontal impaction was the most prevalent type of mandibular third molar impaction in the studied Chennai population. Significant gender variation was observed in impaction patterns, with males showing a greater tendency toward horizontal impaction and females demonstrating higher prevalence of mesioangular impaction. Early radiographic assessment of impacted mandibular third molars is essential for accurate diagnosis, prevention of associated complications, and effective surgical treatment planning